Life history, diagnosis, and biological aspects of Engytatus varians (Hemiptera: Miridae), a predator of Bactericera cockerelli (Hemiptera: Triozidae). Issue 8 (2nd August 2016) - Pineda, Samuel; Medina, Manuel; Figueroa, José I.; Henry, Thomas J.; Mena, Laura V.; Chavarrieta, Juan M.; Gómez, Benjamín; Valdez, Jorge M.; Lobit, Philipphe; Martínez, Ana M.
ABSTRACT: The life cycle and several life parameters of the zoophytophagous predator Engytatus varians (Distant) (Heteroptera: Miridae), including nymphal growth according to Dyar's rule, were examined in the laboratory. The egg, nymph (five instars), and adult stages were 9.20, 17.36, and 19.02 d in length, respectively. The growth ratio for nymphs was consistent with Dyar's rule based on the lengths of the femora of the forelegs, the tibiae and femora of the middle legs, and the antennae. Some biological characteristics of E. varians were also evaluated when the mirid was fed three different diets ( B. cockerelli third instars, Sitotroga cerealella Olivier [Lepidoptera: Gelechiidae] eggs, and a mixture of both instars and eggs). The length of the nymphal stage was three days longer on a diet of only S. cerealella eggs than when the mirids were fed the third instars of B. cockerelli only or a mixture of both. The sex ratio was not affected by the type of diet. Nymphs of E. varians consumed B. cockerelli nymphs (80–85) when fed third instars only and third instars +  S. cerealella eggs, respectively. The potential use of this predator as a biological control agent of B. cockerelli is discussed.